Increased prevalence of psoriasis in patients with coronary artery disease: results from a case–control study. (11th August 2014) - Picard, D.; Bénichou, J.; Sin, C.; Abasq, C.; Houivet, E.; Koning, R.; Cribier, A.; Veber, B.; Dujardin, F.; Eltchaninoff, H.; Joly, P.
Summary Background The incidence of myocardial events has been reported to be increased in patients with psoriasis. Objectives To investigate whether psoriasis is an independent risk factor for coronary artery disease (CAD). Methods We compared the prevalence of psoriasis between case patients with a diagnosis of CAD based on coronary angiography findings and control patients with no CAD referred to the emergency surgery department for an acute noncardiovascular condition. Case and control patients were examined for the presence of psoriasis by two dermatologists. The prevalence of psoriasis was compared among patients with CAD according to CAD severity. Five‐hundred cases and 500 age‐ and sex‐matched controls were included. Results Using matched univariate analysis, the prevalence of psoriasis was about twofold higher in CAD case patients than in control patients [8·0% vs. 3·4%, odds ratio (OR) 2·64; 95% confidence interval (CI) 1·42–4·88]. Using unconditional multivariate analysis, the association of psoriasis with CAD appeared to be borderline significant (OR 1·84; 95% CI 0·99–3·40). Psoriasis in patients with CAD was significantly associated with three‐vessel involvement relative to one‐or two‐vessel involvement (13·1% vs. 6·1%; OR 3·07; 95% CI 1·50–6·25). Conclusions The prevalence of psoriasis is twofold higher in patients with CAD than in control patients without CAD. It is associated with a more severe coronary artery involvement.